Sex differences in murine MASH induced by a fructose-palmitate-cholesterol-enriched diet - Lakshmi Arivazhagan; Sofie Delbare; Robin A. Wilson; Michaele B. Manigrasso; Boyan Zhou; Henry H. Ruiz; Kaamashri Mangar; Ryoko Higa; Emily Brown; Huilin Li; Michael J. Garabedian; Ravichandran Ramasamy; et al. (JHEP Reports)
Background & Aims: Metabolic syndrome-associated steatotic liver disease (MASLD) and metabolic syndrome-associated steatohepatitis (MASH) have global prevalence rates exceeding 25% and 3-6%, respectively. The introduction of high-fructose corn syrup to the diet in the 1970s has been linked to metabolic and hepatic disturbances. Despite these associations, the potential for sex-dependent responses resulting from fructose-containing diets on MASLD/MASH has not been addressed. Methods: Female and male C57BL/6J mice were fed a fructose-palmitate-cholesterol (FPC)-NASH diet vs. standard chow for 16 weeks (n = 40 mice). At sacrifice, plasma and liver were retrieved, the latter for single-nucleus RNA sequencing. Publicly available data sets of human male and female MASH liver were probed. Results: The FPC-NASH diet-induced metabolic dysfunction in both female and male mice, with females exhibiting more severe hepatic steatosis (p = 0.0262), inflammation (p = 0.0206), and fibrosis (p <0.0001). Single-nucleus RNA sequencing revealed distinct sex-specific transcriptional profiles in hepatocytes and stellate cells responding to the FPC-NASH diet compared to the standard chow. In female mice, compared to males, pathways associated with lipid and metabolic processes in hepatocytes and cell-cell communication and adhesion in stellate cells were enriched. Metabolic flux analyses demonstrated reduced bile acid metabolism in female mice and human hepatocytes in FPC-NASH and MASH conditions, respectively, compared to their male counterparts. Conclusions: Molecular profiling of hepatocytes and stellate cells in FPC-NASH diet-fed mice revealed significant sex differences mirrored in human MASH. The identification of intrinsic, within-sex, diet-dependent disparities underscores the critical need to include both male and female individuals in MAFLD/MASH studies and clinical trials. Impact and implications:: Despite the importance of metabolic dysfunction-associated steatohepatitis (MASH) in impairment of human health, the potential for and mechanisms of sex-dependent responses have yet to be well-studied, particularly with respect to the possible influence of high-fructose corn syrup additives to the diet, which has been linked to metabolic and hepatic disturbances. In a mouse model of fructose supplementation to a NASH diet, female mice displayed significantly higher MASH scores (steatosis, inflammation and fibrosis) compared to male mice. Single-nucleus RNA sequencing of livers revealed intrinsic, diet-dependent molecular disparities within sex, which were exaggerated when comparing female vs. male mice fed the fructose-containing NASH diet; many of these findings were recapitulated in human female vs. male patients with MASH. These results highlight potential mechanistic explanations and therapeutic targets for addressing sex differences and underscore the need to study both sexes in animal models and human MASH.